Pengaruh Diklat, Disiplin Dan Motivasi Kerja Terhadap Kinerja Pegawai Kantor Wilayah Direktorat Jenderal Bea Dan Cukai Sulawesi Bagian Selatan - Ahmad Gani, Ackhriansyah; Irdayani, Sulistia (Jurnal Online Manajemen ELPEI, 2023)
This study aims to examine the Effect of Training, Discipline and Work Motivation on the Performance of Regional Office Employees of the Directorate General of Customs and Excise in Southern Sulawesi. This research was conducted at the Regional Office of the Directorate General of Customs and Excise for Southern Sulawesi (Kanwil DJBC Sulbagsel) which is located on Jl. Satando No. 94, Malimongan Tua, Kec. Wajo, Makassar City, South Sulawesi with research time starting from November to December 2022. The population of this study were employees at the Regional Office of the Directorate General of Customs and Excise in Southern Sulawesi (Kanwil DJBC Sulbagsel), in selecting the sample we used a census or comprehensive method so that the entire population would be used as a sample in this study so that a total of 74 respondents were obtained. This study uses field research methods. The type of data we use in this study is quantitative data, while the data source is primary data. To collect field data, this study used a survey method by distributing questionnaires. The statistical method used to test the hypothesis is by using multiple linear regression with the help of SPSS software. The results of the analysis show that the variables of internal control, discipline and work motivation have a positive and significant effect on the employee performance of the DJBC Sulbagsel Regional Office of Staff.